The Monsanto papers : deadly secrets, corporate corruption, and one man's search for justice - Gillam, Carey (Island Press, 2021)
"The Monsanto Papers is the inside story of Lee Johnson's landmark lawsuit against Monsanto, a David-and-Goliath showdown pitting a dying cancer victim and an eclectic team of young, ambitious lawyers against one of the world's most powerful corporate giants. For Lee, the case was a race against the clock, with doctors predicting he wouldn't survive long enough to take the witness stand. For the public, the legal challenge presented a question of corporate accountability. With enough money and influence, could a company endanger its customers, hide evidence, manipulate regulators, and get away with it all--for decades?"--